1996
DOI: 10.1080/03079459608419178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofSalmonella enteritidis‐immune lymphokines on host resistance toSalmonella entericaser.gallinaruminfection in broiler chicks

Abstract: The prophylactic treatment of neonatal broiler chicks with lymphokines derived from S. enteritidis-immurazed chickens (SE-ILK) was evaluated for its effect on the birds' resistance to an experimental infection S. enterica ser. gallinarum (SG). On the day of hatch, chicks were injected intraperitoneally with either SE-ILK, control non-immune lymphokines (NILK), or were left untreated. Thirty minutes later, all chicks were orally gavaged with either 10(4) colony forming units (CFU) or 10(6) CFU SG. The chicks we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…The cytokine-mediated protection was generated when administered prophylacticall y either in ovo at 18 days of embryogenesis or orally, subcutaneously, or nasally at hatch (McGruder et al, 1995a,b;Genovese et al, 1998b;Kogut et al, 1998). Poultry administered this cytokine soup were protected from vertical and horizontal transmission of paratyphoid and typhoid salmonellae infections (McGruder et al, 1993;Kogut et al, 1996;Lowry et al, 1997;Ziprin & Kogut, 1997;Lowry et al, 1999). This cross-protection between serotypes, regardless of antigenic differences, is in contrast to most Salmonella vaccines (reviewed in Cooper et al, 1994).…”
Section: Cytokines As Therapeutic Agentsmentioning
confidence: 88%
See 2 more Smart Citations
“…The cytokine-mediated protection was generated when administered prophylacticall y either in ovo at 18 days of embryogenesis or orally, subcutaneously, or nasally at hatch (McGruder et al, 1995a,b;Genovese et al, 1998b;Kogut et al, 1998). Poultry administered this cytokine soup were protected from vertical and horizontal transmission of paratyphoid and typhoid salmonellae infections (McGruder et al, 1993;Kogut et al, 1996;Lowry et al, 1997;Ziprin & Kogut, 1997;Lowry et al, 1999). This cross-protection between serotypes, regardless of antigenic differences, is in contrast to most Salmonella vaccines (reviewed in Cooper et al, 1994).…”
Section: Cytokines As Therapeutic Agentsmentioning
confidence: 88%
“…It is during this first 4 days post-hatch that innate defense mechanisms must function to prevent Salmonella from multiplying to numbers capable of overwhelming any response that is generated. From all of the studies reported, the administration of these cytokines induce protection against salmonellae within 24 h (McGruder et al, 1993(McGruder et al, , 1995aTellez et al, 1993;Kogut et al, 1996). Moreover, the protection conferred by the cytokines lasts only 5 to 10 days (McGruder et al, 1995a;Kogut et al, 1996;Genovese et al, 2000).…”
Section: Cytokines As Therapeutic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have further shown that IFN-γ can activate in vitro heterophil functional activity against Salmonella ( Kogut et al., 2001 ; Kogut et al., 2005 ) and the presence of IFN-γ and IL-2 in a S . Enteritidis immune cytokine cocktail protects day-old chicks against Salmonella infections mediated by activated heterophils ( Kogut et al., 1996 ; Verduzzo et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enteritidis, produce una inmunidad mediada por linfoquinas que reduce la transmisión horizontal de S. Gallinarum (67). La exclusión competitiva también ha sido intentada para controlar el tifus aviar utilizando S. Enteritidis o S. Gallinarum (68).…”
Section: )unclassified